Analysis of the Effectivenes of Utilization Book Proposal Web Service on the Availability and Completeness of New Collentions at the Trenggalek Regency Archives and Library Office - Aulia, Aura; Sari, Nadia Roosmalita (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: The development of information technology has encouraged libraries to adopt innovations in their services, one of which is through a book proposal web service.Objective: This study aims to analyze the effectiveness of the utilization of the book proposal web service on the availability and completeness of new collection at the Trenggalek Regency Archives and Library.Methods: This research employs field research with a qualitative descriptive approach based on the DeLone and McLean Information Success Model (2003), which consisst of six main indicators. Data collection includes observations and interviews with four users of the book proposal web service. The collected data was then analyzed using data reduction, data presentation, and conclusing drawing.Results: The result indicate that the book proposal web provides easy access for users, several challenges remain, such a lack of clarity regarding proposal status, delays in follows-ups suboptimal system reliability, and suboptimal system reliability. Despite these challenges, the service contribute are still to aligning the library’s collection with user’s needs, though some book categories are still considered incomplete.Conclusion: Based on the research results, it is necessary information transparency, optimize follow-up of proposals, and improve the system to be more stable so that this service can be more effectivein increasing library collections according to user needs.